Digital Social Movements and Political Participation of the Indonesian Millennial Generation: Research Trends Based on Bibliometric Analysis Using VOSviewer and Biblioshiny - Anwar, Rully Khairul; Fauzianty, Herlin Aprilya (TEMALI : Jurnal Pembangunan Sosial, 2025)
This study aims to map trends and identify key issues in the literature on digital social movements and political participation of the millennial generation in Indonesia, a topic that requires a deeper understanding in line with technological developments and socio-political dynamics. Quantitative bibliometric analysis was used to analyze scientific publication data indexed in Scopus. The data collection technique involved downloading bibliographic data in CSV format from Scopus, with filters for the publication period 2014-2024, article document type, and relevant keywords. The collected data was then analyzed using VOSviewer, Biblioshiny, and RStudio software for network visualization, co-occurrence analysis, and publication trend mapping. The results showed consistent annual publication growth on this topic, indicating increasing interest and relevance of the issue of digital social movements and millennial political participation. The three most dominant and interrelated keywords are social movement, youth, and political participation, highlighting the central role of young people in contemporary socio-political dynamics. Further analysis identified nationalism, election, and popular protest as concepts that have the potential to be the focus of further research, especially in the context of the use of social media by the millennial generation. This research contributes to the development of literature on social movements in the digital era, especially in the Indonesian context. These findings provide new insights into the relationship between digital media and millennial political participation and offer practical implications for developing strategies for empowering young people in modern democracies.